Perception and Practice of Blood Donation Among Medical Students in Southern Rajasthan, India - Samanta, Matariswa; Kumar, Dilip L; Patel, Mehul; Mangal, Nitesh; Varghese, K. A. (Nepalese Medical Journal, 2021)
Introduction: Despite all efforts, there is a gap in the demand and supply of blood donation in India. Medical students play a crucial role in promoting and mobilizing blood donation among potential youth. The present study attempted to ascertain the knowledge, attitude, and practice as well as factors associated with actual blood donation among medical students at various stages of their studies. Materials and Methods: The cross-sectional study was conducted during May-June 2021using a pre-tested semi-structured questionnaire through Google form among 346 medical students representing first, second and third-year MBBS. The aggregate scores for knowledge and attitude worked out for each student and analyzed for gender effect, actual practice, a correlation between knowledge and attitude score, and factors contributing to it using z- test, correlation coefficient test, and chi-square test respectively. Results: The blood donation by students was found significantly associated with sex, age, and phases of the MBBS curriculum (p<0.05). The mean attitude score of female students (6.90) was higher compared to male students (6.60). There was a significant correlation (r=0.371) between the overall knowledge and attitude score of students towards blood donation. Conclusions: The gender, age, and phase of study of medical students are significant factors contributing to actual blood donation. The higher attitude of female students could not be transformed into the actual practice of blood donation. Special efforts are required to enthuse medical students in general and female students in particular towards blood donation.